The Correlation between Marine Fishery Economy, Fishermen's Fishery Investment and Fishery Science and Technology Progress based on VAR Model: A Case Study of Zhoushan Fishery - Xu, Bo (Journal of Global Economy, Business and Finance, 2024)
The economic growth of marine fisheries is an important driving force for the high-quality development of the marine economy. Technological innovation in marine fisheries and investment in fishermen's fisheries are two basic elements that promote the economic growth of marine fisheries. However, there is little literature that delves into the internal relationship between the three. This article first constructs a model for the internal relationship between fishermen's fishery investment, fishery technology innovation, and marine fishery economic growth, and captures relevant data on marine fisheries in Zhoushan City from 2000 to 2021. Based on this, a VAR model is used for empirical research. The research results indicate that: (1) there is a significant positive mutual promotion effect between fishermen's fishery investment and marine fishery economic growth; (2) The progress of marine fishery technology and the growth of marine fishery economy also have a significant positive mutually promoting effect; (3) The investment expenditure of marine fishermen on fisheries has a certain positive effect on the progress of marine fishery technology, but the progress of marine fishery technology has no impact on the investment expenditure of fishermen on fisheries. Therefore, in order to achieve high-quality development of the marine economy, attention should be paid to the guidance of fishermen's fishery investment, further improve the market protection mechanism of fishermen's investment expenditure, and strengthen technological innovation in marine fisheries to promote high-speed growth of the marine fishery economy.